Over-expression of potato virus X TGBp1 movement protein in transgenic tobacco plants causes developmental and metabolic alterations - Kobayashi, Ken (2004)
Transgenic Nicotiana tabacum plants expressing the TGBp1 movement protein of potato virus X (PVX) were studied to investigate the effects caused by this protein on plant physiology and development. TGBp1 caused consistent reductions of size and weight in different organs of these plants; however shoot-to-root ratios were similar to those of control plants. Transgenic seedlings showed smaller root meristems and calli derived from TGBp1 leaves grew at a slower rate through successive subcultures. Microscopic observations of TGBp1 plants revealed flattened chloroplasts containing plastoglobuli-like bodies. Further analyses showed a considerable reduction in photosynthetic rate, lower starch levels in leaves and roots, higher nitrate accumulation in leaves and induction of pathogenesis-related (PR) protein genes. Since these changes were not observed when other PVX sequences were expressed in tobacco, we postulate that TGBp1 is an important symptom contributor in PVX infections.